Central American Elites and Investment Diversification: Water Markets in Guatemala and Costa Rica - Retana Céspedes, Juan Manuel (2019)
This research studies the insertion of the Diversified Business Groups in the water markets in Guatemala and Costa Rica is studied through the characterization of the “green” model of water conservation and custody, as well as the monetization mechanisms and the new strategies of capitalism. The diversification of these groups towards “green” economic niches responds to the platform provided especially by the World Bank for investments in water and other natural goods, providing financial security to these businesses. It is concluded that although it does not imply a privatization as such, these strategies of monetization and accumulation in a few hands of water use rights put at risk the availability for other people, the welfare of nature and the fundamental human right of access to this liquid.